Occurrence of cross-resistance and β-lactam seesaw effect in glycopeptide-, lipopeptide- and lipoglycopeptide-resistant MRSA correlates with membrane phosphatidylglycerol levels. (4th February 2020) - Hines, Kelly M; Shen, Tianwei; Ashford, Nathaniel K; Waalkes, Adam; Penewit, Kelsi; Holmes, Elizabeth A; McLean, Kathryn; Salipante, Stephen J; Werth, Brian J; Xu, Libin
Abstract: Background: Glycopeptides (GPs), lipopeptides (LPs) and lipoglycopeptides (LGPs) are related antimicrobials important for the management of invasive MRSA infections. Cross-resistance among these antibiotics in MRSA is well documented, as is the observation that susceptibility of MRSA to β-lactams increases as susceptibility to GPs and LPs decreases (i.e. the seesaw effect). Efforts to understand the relationship between GP/LP/LGP cross-resistance and the seesaw effect have focused on the PBPs, but the role of lipid metabolism has not been investigated. Objectives: Since the cell membrane is structurally and metabolically integrated with the cell wall and anchors associated proteins, including PBPs, we examined the relationship between membrane lipid composition and the phenomena of cross-resistance among GPs/LPs/LGPs and the β-lactam seesaw effect. Methods: We selected for daptomycin, vancomycin and dalbavancin resistance using the USA300 strain JE2 and evaluated the resulting mutants by WGS, MS-based lipidomics and antimicrobial susceptibility testing to assess the relationship between membrane composition, cross-resistance, and the seesaw effect. Results: We observed cross-resistance to GPs/LPs/LGPs among the selected strains and the seesaw effect against various β-lactams, depending on the PBP targets of the particular β-lactam. We found that modification of membrane composition occurs not only in daptomycin-selected strains, but also vancomycin- and dalbavancin-selected strains. Significantly, we observed that the abundance of most phosphatidylglycerols positively correlates with MICs of GPs/LPs/LGPs and negatively correlates with the MICs of β-lactams. Conclusions: These studies demonstrate a major association between membrane remodelling, cross-resistance and the seesaw effect.